Effect of Physical Exercises, Fartlek Training and Combined Training on Speed among Men Trainee Sub Inspectors of Andhra Pradesh: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The present study was undertaken to analyze the effect of physical exercises, fartlek training and combined training on speed among men trainee sub-inspectors of Andhra Pradesh. The researcher selected sixty four men trainee sub-inspectors were from beachpally, Andhra Pradesh. Their age ranged from 21 to 25 years. The subject chosen for the study divided into four equal groups and designed fartlek training group (FTG), Physical exercise group (PEG) and fartlek training with physical exercise programme (FTPEG) and control group (CG). Experimental groups underwent for twelve weeks of training program on alternative days. The data were selected before and after the training period. The collected data analysed with analysis of covariance (ANCOVA). The level of significant was fixed at 0.05 levels. Where ever the ‘F’ ratio found significant Scheffe’s post-test was used for find out the significant differences among the adjusted paired mean. The result of the study concluded that FTG, PEG and FTPEG are significantly improved speed level when compared with control group.